Bioethanol production as biofuel from potato peel using Saccharomyces cerevisiae PTCC 5052 and Zymomonas mobilis PTCC 1718 (Bioagro, 2020)
Bioethanol is a renewable and environmentally friendly fuel with minimum contamination that can be obtained from the fermentation or distillation of several raw materials. In the present research, potato peel waste was used as a pure carbon source due to its high fermentable carbohydrate content. In order to promote the conversion of starch to glucose, acid hydrolysis, as a low cost method was used. Two types of microorganisms including Saccharomyces cerevisiae and Zymomonas mobilis were used to synthesize the bioethanol. The effect of different biochemical conditions (fermentation time and yeast extract concentration) was assessed on the ethanol yield in both types of microorganisms. The results showed that the best fermentation time for Z. mobilis occurred after five days, and the best yeast extract concentration added to fermentation was 3 g·L-1, which had the highest yield for bioethanol production (0.521 %). The best fermentation time for S. cerevisiae was obtained after seven days without adding yeast extract, which had the highest yield for bioethanol production (0.180 %). In conclusion, the results obtained here showed that Z. mobilis had the best performance in the synthesis of bioethanol from potato peels, and the duration of 120 hours for fermentation in both microorganisms led to better results for ethanol production due to approaching the stationary phase.
Keywords: Acid hydrolysis; fermentation; organic wastes; yeasts